The relationship between triglyceride level and the severity of acute hypertriglyceridemic pancreatitis in Chinese patients - Sun, Ya Mei; Gao, Feng; Chen, Xue; Zhang, Jie (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To investigate the relationship between the triglyceride (TG) level and the severity of acute hypertriglyceridemic pancreatitis (AHTGP) in Chinese patients.Materials and Methods: Based on clinical data on AHTGP, patients from the period 2015–2018 were enrolled retrospectively and grouped according to the 2012 revised Atlanta classification. The Kruskal–Wallis test was performed to evaluate differences among groups. Receiver operating characteristic (ROC) curves were generated to assess the ability of parameters to distinguish MAP/MSAP from SAP.Results: A total of 104 patients with AHTGP was enrolled and divided into three groups: 61 patients with mild acute pancreatitis (MAP), 29 patients with moderately severe acute pancreatitis (MSAP), and 14 patients with severe acute pancreatitis (SAP). The median values for the MAP, MSAP, and SAP groups were as follows: TG level 48 h after admission, 3.4, 4.5, and 14.2 mmol/L, respectively (P < 0.001); ratio of TG level 48 h after admission to that 0 h after admission (48:0-h ratio), 19.4, 32.1, and 65.9, respectively (P < 0.001). Receiver operating characteristic curves showed that the areas under the curves for the TG level 48 h after admission and the TG 48:0-h ratio for predicting SAP were 0.965 and 0.917, respectively (P < 0.001), and the optimal cut-off values were 7.8 mmol/L and 37.7, respectively.Conclusion: The TG level 48 h after admission and the TG 48:0-h ratio may predict the severity of AHTGP, and a high TG level 48 h after admission may be correlated with the progression of SAP.